(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In this article the analysis of a contribution of children’s literature of the patriot I. Altynsarin is carried out, for the first time taken in hand work of national education and throughout all the life continuously working over these questions. The pedagogical life of I.Altynsarin, his contribution to development of the Kazakh culture, activity as poet and the writer are considered, taking the place in stories of the Kazakh literature, thematic and educational feature of its such works, of: «Kel balalar okilik», «Oner bilim bar zhurttar», «Taza bulak», «bay balasi men zharli balasy».